SiO₂/Au core-shell nanoparticles: synthesis and characterization - Matveevskaya, N.A.; Tolmachev, A.V.; Pazura, Yu.I.; Savvin, Yu.N.; Dukarov, S.V.; Semynozhenko, V.P. (Functional Materials, 2005)
Preparation of heteronanoparticles of the core-shell type has been described based on single-dispersed spherical nanoparticles of silicon dioxide and gold. Using the colloid chemistry techniques, nanoparticles having different dielectric core diameters and different metal shell thickness have been obtained. The effect of the nanoparticle structure on the absorption spectra thereof has been investigated. The maximum position in the absorption spectra has been shown to be defined by dielectric core diameter ratio to the gold shell thickness in the SiO₂/Au nanoparticles.